Improving Early Childhood Creative Thinking Skills Through Nature-Based Loose Parts Media - Maghfirotul Qiromah, Istianah; Hadi Pradana, Pascalian; Hasanah, Hisbiyatul (Jurnal Pendidikan Anak, 2023)
Today’s age, many children seem to be less interested in learning at school. This could be because they arespending more time playing with gadgets at home instead of studying. As a result, their creativity andcritical thinking skills are not being optimally developed. To address this issue, researchers have tried toimprove children’s creative thinking abilities by using nature-based loose part media. They conductedan action classroom research with 20 children to evaluate the impact of this approach on their creativethinking skills. The researchers observed indicators such as the children’s curiosity, imagination, ability toproduce forms, and sense of responsibility. The results showed that using nature-based loose part mediacan significantly enhance young children’s creative thinking abilities. In pre-cycle, 11 children showedhigh achievement in creative thinking abilities, but this number increased to 15 children in cycle I and 19children in cycle II. Therefore, it is crucial for educational institutions to use nature-based loose part mediaduring early childhood learning activities to promote children’s creativity and critical thinking skill